Policyholder and Insurance Policy Features as Determinants of Life Insurance Lapse - Evidence from Croatia - Ćurak, Marijana; Podrug, Doris; Poposki, Klime (Economics and Business Review, 2015)
According to theoretical and empirical literature, life insurance lapse is determined by macroeconomic and insurer-specific factors, demographic and economic features of the policyholder as well as specific characteristics of the life insurance policy. Existing empirical literature on determinants of life insurance options is dominantly focused on developed insurance markets. The aim of this paper is to investigate the drivers of lapse in Croatia using survey data. The research encompasses both policyholder and life insurance contract features. The results of the research show that the number of children, income level, and the financial status of policyholder as well as the duration of the life insurance policies influence policyholders' decisions to lapse life insurance.